Changes in Pre-Service Teacher Personal and Professional Attitudes Following a Comprehensive School Health Course - Nutter, Sarah; Saunders, Jessica F.; Brun, Isabel; Exner-Cortens, Deinera; Russell-Mayhew, Shelly (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2022)
Comprehensive school health (CSH) is a framework that can support teachers in the delivery of health-related content as well as supporting health promotion within the school community. In this study, 222 Bachelor of Education students completed surveys at the beginning and end of a mandatory six-week course on CSH with a body weight-neutral focus. Following the course, participants had significantly positively increased attitudes toward CSH, self-efficacy to teach using CSH, and weight-related attitudes. These results support CSH as a useful framework for teachers in their future practice to improve the wellness of students, teachers, and the broader school community.